Short Communication: Using RAPD technique to evaluate genetic diversity of longan (Dimocarpus longan) population in Vietnam - VIET THE HO; QUOC NGUYEN NGO (Biodiversitas Journal of Biological Diversity, 2017)
Ho VT, Ngo QNg. 2017. Short Communication: Using RAPD technique to evaluate genetic diversity of longan (Dimocarpus longan) population in Vietnam. Biodiversitas 18: xxxx. Longan (Dimocarpus longan L.) is an important fruit plant in Vietnam where several cultivars and landraces are being cultivated. Presently, the identification of longan cultivars and landraces is mainly based on personal experience relying on morphological traits leading the difficulty of genetic conservation and longan breeding. In this study, genetic richness and relativeness of 36 longan accessions collected from different provinces in Vietnam were evaluated by using 30 Random Amplified Polymorphic DNA (RAPD) primers. Our results reveal that there is the large variation of genetic background of studied longan accessions with separate groups in the obtained dendrogram. We also identified the combination of different RAPD markers could help to identify 15 longan genotypes. The results from this project could provide valuable information which is necessary for classifying, identifying plant origins, breeding and conserving programs of longan in Vietnam.